Factor influencing students’ spending habits towards their financial knowledge: case study in UiTM Campus Samarahan 2 / Nur Izzatie Mohamad Shukori and Siti Nurfaizah Nikman Muhammad Usman - Mohamad Shukori, Nur Izzati; Muhammad Usman, Siti Nurfaizah Nikman (2024)
A robust grasp of personal finance, budgeting, and financial planning significantly influences students' spending habits. When students possess this understanding, they tend to make informed and responsible spending choices, prioritizing needs, establishing realistic budgets, and saving for future goals. Conversely, a deficiency in financial knowledge can result in impulsive spending, accumulating debt, and experiencing financial stress. Therefore, a clear link exists between financial literacy and the capacity to manage spending effectively among students. This study aims to identify the determinants influencing spending habits of UiTM Campus Samarahan 2 students, utilizing a proposed sample size of 341. Therefore, the most dominant factors are peer influence. Factor of peer influence is the most influential factor that influences students’ spending habits. There is a significant relationship between knowledge of financial management, parental income and peer influence which will influence the factors that influencing students’ spending habits towards their financial knowledge and there is no significant impact on peer influence ofthe students across gender, between males and females. The data collected through a survey distributed via Google Form Simultaneously, the research seeks to explore the interconnection between financial management knowledge, parental income, peer influence, and the student spending habits towards their financial knowledge in Campus Samarahan 2.